Hezbollah Involvement in Israel-Hamas War: Causes and Implications 2023-2024 - Agubamah , Edgar; Theresa, Odigbo Stephanie (Kashere Journal of Politics and International Relations, 2024)
Hezbollah is a well-known non state actor in the world, especially in the Middle East. In fact, it is the most militarily equipped and organised non state actor in the world. It also has a well networked social service arm and political administration amongst its members. Hezbollah is situated in Lebanon, precisely in the southern part. These exceptional sterling qualities made people to designate the robust militia organization as a state within a state. Hezbollah’s objectives are to rid Lebanon of foreign occupiers, freedom of the Arab world, and to establish Islamic shite state in the area. From their aims one can easily see why Hezbollah is hell bent in attacking Israel or supporting her enemies. In this work our focus is to examine the causes or factors that pushed Hezbollah to engage in the Israel-Hamas war and by extension look at its implications. To effectively, do this we sought for data using documentary evidence from textbooks, journals, Newspapers, Magazines and internet materials. In addition, we use the non-state actor’s theory as an analytical tool. The study discovered that factors like historical, ideology, political, and regional dynamics pushed Hezbollah into engaging in the Israel-Hamas conflict while issues like escalation of violence, humanitarian casualties, dragging of global state actors into the crisis, regional instability, strategic diversion and complication of diplomatic effort to settle the crisis are seen as the implications. Be that as it may, the study recommends that both Israel and Hezbollah should refrain from belligerency and rather embrace dialogue and other diplomatic lee ways.